REGULASI MEDIA SOSIAL DAN PENANGANAN DISINFORMASI ANALISIS KOMPARATIF KEBIJAKAN KOMUNIKASI DI INDONESIA DAN ASEAN - Nasution, Mahardhika Sastra; Sazali, Hasan (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2025)
Handling disinformation in the digital era is a significant challenge for many countries, including Indonesia and countries in the ASEAN region. The spread of disinformation through social media can threaten social, political, and economic stability. This study aims to analyze social media regulation in the context of handling disinformation in Indonesia and compare it with communication policies in several other ASEAN countries. With a qualitative approach, this study collects data from primary sources such as policy documents and interviews with various stakeholders. The findings show that while there are similarities in regulatory efforts, such as the implementation of anti-hoax laws and strengthening the role of supervisory agencies, there are striking differences in the implementation and effectiveness of policies in each country. In Indonesia, the main challenge lies in law enforcement and the level of digital literacy of the community. Meanwhile, countries like Singapore are implementing a stricter approach with strict enforcement and severe sanctions for violators. This study recommends the need for more intensive regional collaboration in tackling disinformation and increasing digital literacy as key steps in combating the spread of misinformation.